Гідрологічний режим ріки Ільця (басейн Чорного Черемошу) - Костенюк, Людмила Володимирівна; Kosteniuk, Liudmyla (Тернопільський національний педагогічний університет імені В. Гнатюка, 2020)
В даній публікації представлено статистичний аналіз даних спостережень на р.Ільця (басейн Чорного Черемошу), зокрема зміни положення кривих Q=f(H), які характеризують направленість вертикальних деформацій та темпи їх розвитку за період з 1959 по 2008 рр.
This publication analyzes the features of the hydrological regime and channel processes of the Iltsya River, based on regular observations and during the expedition trip in June 2019. The schemes of basin distribution and geomorphological zoning of the studied object, curves of connection of water consumption and levels Q = f (H), graphs of the course of maximum, average and minimum water levels, and also cross sections on key sites are presented in the work.
Keywords: hydrological regime, water runoff, sediment runoff, channel processes, geomorphological zoning, cross section area.